The New Breed: How to Re-Imagine Living with Robots - Grommé, Francisca; Odendaal, Adriaan; Ten Berge, Jannes (Journal of Human-Technology Relations, 2023)
In The New Breed: How to Think About Robots (2021), Kate Darling argues that to understand our future with robots a lot can be learned from studying our relationship with animals. The animal analogy raises important new questions, can help to design our futures with robots, and helps to develop an approach to robot rights. However, as Darling also acknowledges, this analogy has limits. First, the question remains whether our relationship with animals, and especially its inconsistent ethics, is a desirable state of affairs. Second, human-animal relationships fall short of offering new ways for humans to care for each other, for animals, and for the technologies they use. Third, most of Darling’s arguments are interlaced with cross-cultural comparisons that demonstrate how we have related to animals in fundamentally similar ways throughout history and across cultures. In this review essay, we turn to the ‘fringes’ or ‘loose ends’ of Darling’s analogy as starting points for thinking with Darling. In particular, we attempt to push forward conversations on human accountabilities and responsibilities in more-than-human relationships.